Gender differences in child to parent violence risk factors - Loinaz, Ismael; Barboni, Lucía; Ma de Sousa, Ava (Anales de Psicología / Annals of Psychology, 2020)
Child-to-parent violence (CPV) has attracted enormous academic interest. Despite this, few studies compare the risk factors between female and male perpetrators of this abuse toward parents. This paper compares 56 male and 35 female CPV offenders, evaluated with the Child-to-Parent Violence Risk assessment tool (CPVR). Results show that girls came from significantly more problematic contexts (with bidirectionality of violence, violence between parents, cohabitation problems and personal problems of parents, and had significantly lower self-esteem. Boys had significantly more histories of substance abuse issues and greater rates of escalation of violence. Overall, both sexes had similar prevalence rates for most variables, the type of violence committed was comparable (although injuries toward fathers were only perpetrated by boys), and female perpetrators had more problematic families than their male counterparts. CPVR scores significantly predicted injuries toward the mother for male offenders (AUC = .842), but not for female offenders (AUC = .660). These results support the use of common treatments and tools for female and male CPV offenders. Future steps and developments in the field are also discussed.